(3GdJfhjQ TQM GdLGeY GdUZjQs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdLGeY dUaGJ GdceGd aEf Gddg hdg GdMeO bO CYGf Ydi TQM GdKdGKI CQHGY ef GdLGeY GdUZjQ , hfQLh efg GdEYGfI Ydi TQM GdQHY GdQGHY s
(3BNQgG (B:s
(3ceG CYfJ Ydi eG SgdJg ef LeY gPG GdTQM , aCSCdc Cf JNdU GdfjI hJUdM GdWhjI hfSCdc MSf GdNJGe ai GdCYeGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHgG HYfGjI GdeDda (B_ (3GHfg ceG hQO ai BNQ GdLRA GdQGHY ef GdfSNI faSgG cJH GdeJf HGdMeQI s
(3CJe GdeDda JCdjag SfI (B1154(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdMOjK h GdeUWdMs